Long-term toxicity of an intraoperative radiotherapy boost using low energy X-rays during breast-conserving surgery - Kraus-Tiefenbacher, Uta; Bauer, Lelia; Scheda, Antonella; Fleckenstein, Katharina; Keller, Anke; Herskind, Carsten; Steil, Volker; Melchert, Frank; Wenz, Frederik (International journal of radiation oncology, biology, physics, 2006)
Purpose: Intraoperative radiotherapy (IORT) as a boost for breast cancer delivers a high single dose of radiation to a late-reacting tissue; therefore late toxicity is of particular interest, and long-term follow-up is warranted. To date there are only limited data available on breast cancer patients treated with IORT using low energy X-rays. We analyzed toxicity and cosmesis after IORT as a boost with a minimum follow-up of 18 months. Methods and Materials: A total of 73 patients treated with IORT (20 Gy/50 kV X-rays; INTRABEAM [Carl Zeiss Surgical, Oberkochen, Germany]) to the tumor bed during breast-conserving surgery as a boost followed by whole-breast radiotherapy (WBRT, 46 Gy) underwent a prospective, predefined follow-up (median, 25 months; range 18 44 months), including clinical examination and breast ultrasound at 6-months and mammographies at 1-year intervals. Toxicities were documented using the common toxicity criteria (CTC)/European Organization for Research and Treatment of Cancer and the LENT-SOMA score. Cosmesis was evaluated with a score from I to 4. Results: The IORT in combination with WBRT was well tolerated, with no Grade 3 or 4 skin toxicities and no telangiectasias. Fibrosis of the entire breast was observed in 5% of the patients. A circumscribed fibrosis around the tumor bed was palpable in up to 27% with a peak around 18 months after therapy and a decline thereafter. The observed toxicitiy rates were not influenced by age, tumor stage, or systemic therapy. The cosmetic outcome was good to excellent in >= 90% of cases. Conclusions: After IORT of the breast using low-energy X-rays, no unexpected toxicity rates were observed during long-term-follow-up. (c) 2006 Elsevier Inc.